Age characteristics of the transformation of psychophysiological functions of operators of unmanned aircraft systems with stressogenic diseases of the digestive organs - Kalnysh, V.V.; Serheta, I.V.; Pashkovskyi, S.M.; Koval, N.V.; Tymchyshyn, T.P.; Trotskyi, O.O. (Environment & Health, 2024)
The purpose of the study is to identify age-related changes in the psychophysiological parameters of operators of unmanned aircraft systems who have stress-associated diseases of the digestive organs. Research materials and methods. In the course of the conducted research, 58 operators of unmanned aircraft complexes aged from 21 to 50 years old who had stress-related diseases of the digestive organs were examined. The investigated operators were divided into 2 groups based on their age. The examination was carried out using blank questionnaires and modern modified methods implemented on the basis of the «PFI-2» software and hardware complex for psychophysiological research. The results. According to the research data, it was established that the probability of diseases of the digestive organs in operators ˂40 years old is 0.78, and in operators ≥40 years old – 0.22 (p=0.00001). Such a large probability gap can be explained by the fact that the young population is particularly prone to the occurrence and development of diseases of the digestive organs. The comparative analysis also demonstrated the fact that most of the psychophysiological parameters of operators with stress-related diseases worsen with age. Correlation analysis showed that according to speed psychophysiological parameters, there is an unreliable shift in the system of ensuring professional activity with age (p=0.53), аccording to the psychological functions, there is a tendency towards the transformation of changes (p=0.0653), and when studying the structure of cognitive characteristics, it weakens quite a lot (p=0.001). Conclusions. It is shown that most of the listed psychophysiological parameters in operators who have stress-associated diseases reliably worsen with age (p